Kaca “Kita Membaca” Buy Book, By Book: Review of Indonesian Literacy - Istiana Ipa; Kurnia Nur Lailah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Background of the problem: According to data from the Organisation for Economic Co-operation and Development (OECD), Indonesia ranks lowest in reading culture among 52 countries in Asia. Purpose: To assist the Indonesian government in increasing reading interest throughout Indonesia, including in remote areas. Method: A quantitative method with correlation research design. Data sources are SD/MI and SMP/MTs students. The result primarily in numerical data which are then analyzed primarily by statistical methods. Result: In this regard, administrators remain neutral and do not involve religious or political matters. Thus, anyone can become a donor regardless of race, ethnicity, religion, or culture, and contribute to the effort of fostering a reading culture for a more prosperous Indonesian society. Implication: Children whose quality and skills are properly honed will have good quality and value in the eyes of society. An online literacy control system is needed, ready to distribute to all provinces in Indonesia with the support of volunteer instructors who directly engage in street activities, provide free book donations, and conduct scientific and artistic skill training. Books received from donors or to be distributed must first be screened for content.